Creating Research Practice Partnerships in Education - Penuel, William R.; Gallagher, Daniel J. (Harvard Education Press, 2017)
"Creating Research-Practice Partnerships in Education" is an invaluable resource for educators and researchers seeking to develop long-term collaborations in which educators and researchers work together to study and solve pressing problems of practice. Drawing on a wide range of examples, the authors describe the purposes for which partnerships may be organized, the forms that these endeavors may take, challenges that they typically face, and strategies for overcoming those challenges. The book includes tools and routines for working together as well as strategies for ensuring equity of participation on both sides. One of the most pressing concerns in education today is bringing research evidence to bear on problems of educational improvement. Research-practice partnerships (RPPs) are drawing new attention as a way to bridge gaps between research and practice. Drawing on the authors' extensive experience in working with RPPs, this book is a practical and insightful guide for those embarking on or engaged in these complex and promising endeavors. [Foreword by John Q. Easton.]